2014
DOI: 10.1159/000368042
|View full text |Cite
|
Sign up to set email alerts
|

Cardiocirculatory Monitoring during Immediate Fetal-to-Neonatal Transition: A Systematic Qualitative Review of the Literature

Abstract: Background: The fetal-to-neonatal transition is a complex process that includes changes in cardiac and respiratory systems. Objective: The aim of this study is to review the different methods of cardiocirculatory monitoring during the immediate neonatal transition period. Methods: A systematic search of PubMed and Ovid Embase was performed using the following terms: infant, newborn, newborn infant, neonate, neonates, heart, cardiac, blood pressure, haemodynamic, hemodynamics, blood circulation, circulation, ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Furthermore, there are 2 noncontinuous methods: measurement of mean arterial blood pressure (MABP) (oscillometric method) and cardiac function (echocardiography) [2,3,4]. In order to guide oxygen therapy, pulse oximetry is recommended by neonatal resuscitation guidelines [5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there are 2 noncontinuous methods: measurement of mean arterial blood pressure (MABP) (oscillometric method) and cardiac function (echocardiography) [2,3,4]. In order to guide oxygen therapy, pulse oximetry is recommended by neonatal resuscitation guidelines [5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…A recent review identified 4 studies of cardiac-output ECHO monitoring during term newborn stabilization [24]. These studies confirm that ECHO assessment of neonatal transition (ductal haemodynamics, and changes in right and left ventricular outputs) is feasible as an objective adjunct to determining newborn haemodynamic status [26,27,28].…”
Section: How To Determine Which Infants Require Vrmentioning
confidence: 91%
“…A number of studies have shown that BP measurements are obtainable in the DR [24,25]. However, such non-invasive BP measurements are not reliably consistent, especially in preterm neonates, and invasive BP monitoring is not practical in the DR setting [3].…”
Section: How To Determine Which Infants Require Vrmentioning
confidence: 99%
“…A recent review by Baik et al identified four studies of echocardiographic monitoring during newborn stabilization ( 42 ). Each study assessed term infants only ( 43 46 ).…”
Section: Peripheral Perfusion Monitoringmentioning
confidence: 99%